Incident heart failure in relation to vascular disease: Insights from the Health, Aging, and Body Composition Study. (27th February 2014) - Khan, Hassan; Kalogeropoulos, Andreas P.; Zannad, Faiez; Marti, Catherine N.; Wilson, Peter W.F.; Georgiopoulou, Vasiliki V.; Kanaya, Alka M.; Newman, Anne B.; Schelbert, Erik; Harris, Tamara B.; Kritchevsky, Stephen; Yancy, Clyde; et al.
<x xml:space="preserve">Abstract</x> Aims The contribution of heart failure (HF) unrelated to vascular disease to the overall HF burden in older adults is not well characterized. This was investigated in this study. Methods and results We assessed HF incidence and outcomes in 2895 participants of the Health ABC Study (age 74 ± 3 years, 48.4% men, 41.4% black) in relation to vascular disease (coronary, peripheral, or cerebrovascular disease) either present at baseline or developed prior to HF. During 11.4 years follow‐up, 493 participants developed HF; 134 (27.2%) in participants without any prior vascular disease and 177 (36.8%) without coronary disease. Both baseline [hazard ratio (HR) 2.4, 95% confidence interval (CI) 1.9–2.8] and incident vascular disease (HR 4.3, 95% CI 3.6–5.2) were associated with HF. During a median follow‐up of 2.1 years after HF onset, 67.5% participants died. Annual mortality after HF development was 21.3% in those with compared with 24.6% in those without vascular disease (HR 1.11, 95% CI 0.87–1.43; P = 0.399). There were 658 all‐cause (436.3/1000 person‐years) and 523 HF‐related (346.4/1000 person‐years) hospitalizations after HF development. There was no significant difference in hospitalizations between those with and without vascular disease [rate ratio (RR) 1.04, 95% CI 0.86–1.24 for all‐cause, and RR 0.84 95% CI 0.69–1.02 for HF hospitalization]. HF with preserved EF was more common in participants without vascular disease (67.0% vs. 55.0%, P = 0.040). Conclusion A significant proportion of HF in older adults develops without prior vascular disease. Outcomes for these patients are poor compared with those with preceding vascular disease. These data suggest the need for more targeted HF prediction and prevention efforts.